Photobiomodulation with 670 nm light ameliorates Müller cell-mediated activation of microglia and macrophages in retinal degeneration. (December 2017) - Lu, Yen-Zhen; Natoli, Riccardo; Madigan, Michele; Fernando, Nilisha; Saxena, Kartik; Aggio-Bruce, Riemke; Jiao, Haihan; Provis, Jan; Valter, Krisztina
Abstract: Müller cells, the supporting cells of the retina, play a key role in responding to retinal stress by releasing chemokines, including CCL2, to recruit microglia and macrophages (MG/MΦ) into the damaged retina. Photobiomodulation (PBM) with 670 nm light has been shown to reduce inflammation in models of retinal degeneration. In this study, we aimed to investigate whether 670 nm light had an effect on Müller cell-initiated inflammation under retinal photo-oxidative damage (PD) in vivo and in vitro . Sprague-Dawley rats were pre-treated with 670 nm light (9J/cm 2 ) once daily over 5 days prior to PD. The expression of inflammatory genes including CCL2 and IL-1β was analysed in retinas. In vitro, primary Müller cells dissociated from neonatal rat retinas were co-cultured with 661W photoreceptor cells. Co-cultures were exposed to PD, followed by 670 nm light treatment to the Müller cells only, and Müller cell stress and inflammation were assessed. Primary MG/MΦ were incubated with supernatant from the co-cultures, and collected for analysis of inflammatory activation. To further understand the mechanism of 670 nm light, the expression of COX5a and mitochondrial membrane potential (ΔΨm) were measured in Müller cells. Following PD, 670 nm light-treated Müller cells had a reduced inflammatory activation, with lower levels of CCL2, IL-1β and IL-6. Supernatant from 670 nm light-treated co-cultures reduced activation of primary MG/MΦ, and lowered the expression of pro-inflammatory cytokines, compared to untreated PD controls. Additionally, 670 nm light-treated Müller cells had an increased expression of COX5a and an elevated ΔΨm following PD, suggesting that retrograde signaling plays a role in the effects of 670 nm light on Müller cell gene expression. Our data indicates that 670 nm light reduces Müller cell-mediated retinal inflammation, and offers a potential cellular mechanism for 670 nm light therapy in regulating inflammation associated with retinal degenerations. Highlights: Photobiomodulation using 670 nm light mitigates Müller cell activation directly, through which it reduces retinal microglia/macrophage activation maintains mitochondrial function in Müller cells thereby supporting retinal homeostasis, and protects photoreceptors following photo-oxidative stress may provide a non-invasive and cost-effective treatment option in retinal inflammatory conditions.